Disease-causing mutations in genes encoding transcription factors critical for photoreceptor development - Sun, Chi; Chen, Shiming (Frontiers in Molecular Neuroscience, 2023)
Photoreceptor development of the vertebrate visual system is controlled by a complex transcription regulatory network. OTX2 is expressed in the mitotic retinal progenitor cells (RPCs) and controls photoreceptor genesis. CRX that is activated by OTX2 is expressed in photoreceptor precursors after cell cycle exit. NEUROD1 is also present in photoreceptor precursors that are ready to specify into rod and cone photoreceptor subtypes. NRL is required for the rod fate and regulates downstream rod-specific genes including the orphan nuclear receptor NR2E3 which further activates rod-specific genes and simultaneously represses cone-specific genes. Cone subtype specification is also regulated by the interplay of several transcription factors such as THRB and RXRG. Mutations in these key transcription factors are responsible for ocular defects at birth such as microphthalmia and inherited photoreceptor diseases such as Leber congenital amaurosis (LCA), retinitis pigmentosa (RP) and allied dystrophies. In particular, many mutations are inherited in an autosomal dominant fashion, including the majority of missense mutations in CRX and NRL. In this review, we describe the spectrum of photoreceptor defects that are associated with mutations in the above-mentioned transcription factors, and summarize the current knowledge of molecular mechanisms underlying the pathogenic mutations. At last, we deliberate the outstanding gaps in our understanding of the genotype-phenotype correlations and outline avenues for future research of the treatment strategies.